Ag/AgBr/Co–Ni–NO3 Layered Double Hydroxide Nanocomposites with Highly Adsorptive and Photocatalytic Properties. Issue 7 (28th December 2012) - Fan, Hai; Zhu, Jianying; Sun, Jianchao; Zhang, Shenxiang; Ai, Shiyun
Abstract A facile anion‐exchange precipitation method was used to synthesize bifunctional Ag/AgBr/Co–Ni–NO3 layered double hydroxide (LDH) nanocomposites by adding AgNO3 solution to a suspension of Co–Ni–Br LDH. The Ag/AgBr nanoparticles were highly dispersed on the sheets of Co–Ni–NO3 LDH. The prepared nanocomposites were used to adsorb and photocatalytically degrade organic pollutants from water. Without light illumination, the nanocomposites quickly adsorbed methyl orange, and the adsorptive capacity, which can reach 230 mg g−1, is much higher than those of Co–Ni–Br LDH, Ag/AgBr, and activated carbon. The photocatalytic activities of the nanocomposites for the removal of dyes and phenol are higher than those of Co–Ni–Br LDH and Ag/AgBr. The proposed method can be applied to prepare other LDH/silver salt composites. The high absorptive capacity and good photocatalytic activity of such nanostructures could have wide applications in wastewater treatment.